EU Memory Politics and Europe's Forgotten Colonial Past. Issue 6 (17th August 2020) - Sierp, Aline
Abstract : Since the 1990s, the European Union has started to enter a policy area that until then had been one of the exclusive prerogatives of the nation state: the public dealing with Europe's bloody past. Within a few years the European Parliament passed several resolutions dealing particularly with the commemoration of human rights violations that took place on the territory of the EU while the European Commission made several funding instruments available aimed at using the realm of memory as a mechanism of public sphere formation. While European efforts for transnational historical remembrance have focused almost exclusively on the Holocaust and National Socialism as well as Stalinism, the EU remains curiously quiet about the memories of imperialism and colonialism. This essay analyzes the conflictual memory constellations at the European level with the aim of explaining why European memory politics are characterized by a sustained focus on specific time periods on the one hand and amnesia on the other. By closely analyzing protocols of the European Parliament (EP), the Justice and Home Affairs (JHA) Council and European Council meetings using frame analysis, the essay digs deep into the complex dynamics lying at the heart of memory contests within the EU and provides a differentiated view on the ways in which memory is continuously dislocated, via resistance, consensus-making and conflict.